Assessing Gross Disproportionality in Climate Change Litigation: The Case for a Justificatory Approach - Linde, Eva (Ottawa Law Review / Revue de droit d’Ottawa, 2024)
Canadian climate change litigation is testing the scope of section 7 of the Charter. The young claimants in La Rose v Canada and Mathur v Ontario argue that governments’ insufficient efforts to reduce greenhouse gas emissions violate their right to life, liberty, and security of the person.This article addresses a central challenge in such litigation. Neither international law nor the Charter provides clear criteria for quantifying the obligations of individual states to reduce greenhouse gas emissions. Under these circumstances, how can courts assess whether Canada’s or Ontario’s policies are insufficient and infringe section 7 interests in a grossly disproportionate manner?The article proposes that courts should not attempt to define absolute mitigation obligations. Rather, the inquiry must be a relative one. Courts should begin by determining the global warming trajectory with which Canada’s and Ontario’s emissions align and then ask whether the harm to section 7 interests expected at that level of warming is justified in light of the cost of achieving further emissions reductions. Because such an evaluation depends on risk assessment and political priority-setting, courts should afford governments a broad measure of deference while demanding that they clearly articulate and justify their choices.